ISLAMIC COMMUNICATION AND DIGITAL RESILIENCE: Patterns of Dakwah and Self-Control among Muslim Millennials in Southeast Asia - Artis, Artis; Erni, Erni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article examines the role of Islamic communication and da‘wah in fostering digital resilience among Muslim millennials in Southeast Asia. In an increasingly fast-paced, fragmented, and polarized digital environment, Islamic preaching faces both ethical challenges and transformative opportunities. Employing a qualitative approach based on literature analysis and conceptual reflection on empirical studies of Islamic communication and digital religiosity, this article explores patterns of da‘wah that contribute to self-control, ethical media engagement, and constructive communicative relations. The findings indicate that the effectiveness of digital da‘wah is not determined by the intensity of normative messaging, but by the quality of dialogical relationships established between preachers and audiences. Dialogical approaches enable da‘wah to function as ethical accompaniment rather than moral control. Core principles of Islamic communication—qaulan ma‘rūfan, qaulan layyinan, and qaulan sadīdan—serve as normative anchors that prevent da‘wah from being absorbed into the logic of virality and digital exclusivism. Furthermore, Qur’anic concepts such as taqwā, tabayyūn, and self-control provide a relevant ethical framework for strengthening digital resilience. This study contributes to Islamic communication scholarship by integrating dialogical da‘wah and Qur’anic ethics within contemporary digital contexts.